Ethics for graduate researchers : a cross-disciplinary approach - Russell, Cathriona, 1965-; Hogan, Linda, 1964-; Junker-Kenny, Maureen (Elsevier insights., 2013)
This edited collection is intended as a primer for core concepts and principles in research ethics and as an in-depth exploration of the contextualization of these principles in practice across key disciplines. The material is nested so that readers can engage with it at different levels and depths. It is unique in that it combines an analysis of complex ethical debates about the nature of research and its governance with the best of case-based and discipline-specific approaches. It deals with the following topics in depth: in the natural sciences, it explores the scientific integrity of the researcher and the research process, human cloning as a test case for the limits to research, and the emerging ethical issues in nanotechnology; in the health sciences, it takes up the question of consent, assent and proxies, research with vulnerable groups and the ethics of clinical trials; in the social sciences, it explores the issues that arise in qualitative research, interviews and ethnography; and in the humanities, it examines contested archaeologies and research in divided societies. Overview of Research Ethics Principles Full text papers from experienced researchers across many disciplines Dialogue with ethicists.